Pelatihan Paper-Based TOEFL untuk Guru-Guru Bahasa Inggris Sekolah Dasar di Kabupaten Lombok Tengah - Farmasari, Santi; Herayana, Desi; Shallaita, Baiq Annisa; Tsaqiila, Thalia Qaulan; Munandar, La Ode Alfin Haris (Universitas Mataram, 2025)
This Community Service Program (PKM) aims at enhancing the professional capacity of elementary school English teachers in Central Lombok through targeted training on the Paper-Based TOEFL. The program seeks to support educators with a comprehensive understanding of the TOEFL test structure, content areas, and effective strategies. By improving teachers' knowledge and skills in these areas, the program contributes to the overall improvement of English language instruction in schools. The training was implemented in four stages: socialization, training and discussion, mentoring and evaluation. The PKM was conducted at SMAN 1 Praya Barat Daya, Central Lombok, with participation from 18 elementary school English teachers across the region. The outcomes of the program indicate an improvement in the teachers’ ability to answer TOEFL questions, particularly in the Structure and Written Expression (SWE) section.